2010
DOI: 10.1051/0004-6361/200913218
|View full text |Cite
|
Sign up to set email alerts
|

Reconnection in weakly stochasticB-fields in 2D

Abstract: We study two-dimensional turbulent magnetic reconnection in a compressible fluid in the gas pressure dominated limit. We use open boundary conditions and start from a Harris current sheet configuration with a uniform total pressure. A small perturbation of the vector potential initiates laminar reconnection at the Sweet-Parker rate, which is allowed to evolve for several dynamical times. Subsequently sub-Alfvenic turbulence is produced through random forcing at small wave numbers. The magnetic field topology n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…This is really a case of small-scale magnetic reconnection, as considered in our previous Section 5.3, and not directly relevant to the issue of reconnection of large-scale flux tubes. Two other numerical studies have recently been made of large-scale magnetic reconnection in 2D, by Loureiro et al (2009) and Kulpa-Dybeł et al (2010), which reach different conclusions. On the one hand, Loureiro et al (2009) had a better resolution but used periodic boundary conditions, which strongly constrain the ability to do averaging of the reconnection rate and the attainment of the steady state for reconnection.…”
Section: D Mhd Turbulence and Reconnectionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is really a case of small-scale magnetic reconnection, as considered in our previous Section 5.3, and not directly relevant to the issue of reconnection of large-scale flux tubes. Two other numerical studies have recently been made of large-scale magnetic reconnection in 2D, by Loureiro et al (2009) and Kulpa-Dybeł et al (2010), which reach different conclusions. On the one hand, Loureiro et al (2009) had a better resolution but used periodic boundary conditions, which strongly constrain the ability to do averaging of the reconnection rate and the attainment of the steady state for reconnection.…”
Section: D Mhd Turbulence and Reconnectionmentioning
confidence: 98%
“…They inferred from their data that the 2D turbulent reconnection rate may be independent of resistivity. On the other hand, Kulpa-Dybeł et al (2010) used smaller data cubes but longer averaging, which is enabled by their outflow boundary conditions. They concluded that the reconnection does depend on resistivity and therefore is slow.…”
Section: D Mhd Turbulence and Reconnectionmentioning
confidence: 99%
“…Loureiro et al (2009) studied two-dimensional turbulent reconnection performing high-resolution simulations in a periodic box for Lundquist numbers up to 5 × 10 4 concluding the existence of a critical threshold of the injection rate above which the reconnection rate is enhanced. Kulpa-Dybeł et al (2010) performed numerical simulations of the LV99 model in two dimensions showing that the relations between the reconnection speed and turbulence properties are different than those predicted by the LV99 model, and the reconnection is not fast in the presence of turbulence, since it still depends on the resistivity. In any case, it is obvious that the difference in physics of magnetic turbulence in 2D and 3D makes two dimentional studies a subject of pure academic interest.…”
Section: A Testing Lv99 Predictions With Mhd Codesmentioning
confidence: 99%
“…3 A comparison between 3D and 2D reconnection in the presence of turbulence is made in Kulpa-Dybe" et al (2010). This work confirmed that the reconnection does depend on the dimensions of the system with the rate of 2D reconnection showing dependence on resistivity.…”
Section: Testing Of Lazarian and Vishniac 99 Modelmentioning
confidence: 56%